Tailor‐Made Microporous Metal–Organic Frameworks for the Full Separation of Propane from Propylene Through Selective Size Exclusion. Issue 49 (15th October 2018) - Wang, Hao; Dong, Xinglong; Colombo, Valentina; Wang, Qining; Liu, Yanyao; Liu, Wei; Wang, Xin‐Long; Huang, Xiao‐Ying; Proserpio, Davide M.; Sironi, Angelo; Han, Yu; Li, Jing
Abstract: Adsorptive separation of olefin/paraffin mixtures by porous solids can greatly reduce the energy consumption associated with the currently employed cryogenic distillation technique. Here, the complete separation of propane and propylene by a designer microporous metal–organic framework material is reported. The compound, Y6 (OH)8 (abtc)3 (H2 O)6 (DMA)2 (Y‐abtc, abtc = 3, 3′, 5, 5′‐azobenzene‐tetracarboxylates; DMA = dimethylammonium), is rationally designed through topology‐guided replacement of inorganic building units. Y‐abtc is both thermally and hydrothermally robust, and possesses optimal pore window size for propane/propylene separation. It adsorbs propylene with fast kinetics under ambient temperature and pressure, but fully excludes propane, as a result of selective size exclusion. Multicomponent column breakthrough experiments confirm that polymer‐grade propylene (99.5%) can be obtained by this process, demonstrating its true potential as an alternative sorbent for efficient separation of propane/propylene mixtures. Abstract : A tailor‐made microporous metal–organic framework designed through a topologically guided secondary building unit (SBU) replacement strategy exhibits the highest selectivity for fast and efficient separation of propane and propylene via a size‐exclusion adsorption mechanism. This material, with excellent thermal and hydrothermal stability, and facile and scalable synthesis, is capable of producing polymer‐grade propylene (99.5%) from a typical propane/propylene mixture of cracking products.